A: Sistem Pakar Mendeteksi Kerusakan Mesin Penggiling Jagung Menggunakan Metode Certainty Factor Pada CV. Central Jagung Persada - Munawarah, Nadila; Ikhwan, Ali (AI Society & STMIK Indonesia, 2024)
A corn grinding machine is a combustion engine that is used to drive a propeller which functions to knock out corn kernels from the cob, so that the release of corn kernels from the cob is very fast and time efficient. This really helps corn farmers and also corn refinery owners to speed up the process to the processing factory. However, in the process of threshing corn from the cobs, the machine often experiences damage, so it is necessary to detect damage to the corn grinding machine with an expert system using the Certainty Factor method in order to help farmers quickly understand what damage is occurring to the machine without having to bring the machine or call someone. machine repair expert, where the system created can also provide solutions related to machine damage. Corn grinding machines that experience fan damage with damage code P01 have a certainty level of damage of 67.2% or Certainty Factor=0.672.